Clonal trial of five genotypes of “camu-camu”, Myrciaria dubia (h.b.k) mc. Vaugh, in non-flooded area - Pinedo Freyre, Sergio Fernando; Imán Correa, Sixto Alfredo; Pinedo Panduro, Mario; Vasquez, Armando; Collazos, Herman (Academic Journals, 2017)
[EN] The objective of this research was to evaluate fruit yield, other agronomic characteristics and content of ascorbic acid (aa) of five promissory genotypes of “camu-camu” in non-flooded area of the experimental field “El Dorado”. The plantation has been established for 4 years and is located in 03° 56’ 50’’S, 73° 25’ 13’’W and 118 a.s.l. altitude, which is part of INIA-EEA“San Roque”4. The clones evaluated were MD-013, MD-014, MD-015, MD-017 and MD-020 and they stood out in the previous analysis in the national camu-camu germplasm collection of INIA. The experiment was established with a completely randomized block statistical design (CRBD) with five treatments and four replications, and each experimental unit consisted of nine plants, with a distance of 3 x 3 m. During the reproductive phenology which was 9 months long, nine variables were evaluated: Leaf length (cm), leaf width (cm), petiole length (cm), number of basal branches, basal branch diameter (cm), number of fruits, fruits weight (g), fruits yield (kg) and ascorbic acid (mg/100 g). As a result, “petiole length” was different statistically (F = 3.96, p = 0.028). The heritability was low for all the variables: “leaf length” (h2 = 0.13), “leaf width” (h2 = 0.06), “basal branches diameter” (h2 = 0.004), “number of fruits per plant” (h2 = 0.17), “ascorbic acid content” (h2 = 0.002), “petiole length” (h2 = 0.43), “number of basal branches” (h2 = 0.33), “weight of fruits per plant” (h2 = 0.29) and “fruits yield” (h2 = 0.26). However, fruit yield showed a range of 2.0 to 2.6 kg / plant (2200 to 2800 kg / ha).